EFFORTS TO IMPROVE THE LEARNING OUTCOMES OF CLASS IX A OF UPT SMP NEGERI 27 GRESIK IN CONGRUENCE AND SIMILARITY THROUGH A COOPERATIVE LEARNING MODEL BASED ON ANIMATION MEDIA - Ninik Nukhrojah (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2022)
Teaching and learning activities are carried out gradually based on its difficulty level. This avoids the assumption that studying at school is difficult, hypothetically regarding mathematics. For UPT SMP Negeri 27 Gresik students, many students complained that mathematics subjects are scary, uninteresting, difficult and do not seem to have any correlation with everyday life. These complaints are the negative perception of mathematics. Meanwhile, there are also students who enjoy the fun of mathematics and are challenged to solve every math problem. These condition is the positive perception of mathematics.From the results of learning activities that have been carried out for three cycles, and based on all the discussions and analyzes, learning activities throughcooperative learning based on animation media has a positive impact on improving student achievement, which is characterized by an increase in student learning completeness in each cycle: cycle I (65.63 %), cycle II ( 78.13 %), and cycle III (93.75 %). The application of cooperative learning based on animation media has a positive influence, which can improve student achievement shown by the average student answers stating that students are interested